2021
DOI: 10.1051/sicotj/2021046
|View full text |Cite
|
Sign up to set email alerts
|

Condylar constrained knee prosthesis and rotating hinge prosthesis for revision total knee arthroplasty for mechanical failure have not the same indications and same results

Abstract: Purpose: This study aimed to evaluate whether there are any differences in outcomes and complication rates between condylar constrained knee (CCK) and rotating hinge knee (RHK) prostheses used for the first revision of total knee arthroplasty (rTKA) after mechanical failure. Methods: Sixty-three consecutive non-septic revisions of posterior stabilized implants using 33 CCK and 30 RHK prostheses were included. Clinical evaluation and revision rate were compared between the two groups at two years minimum follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
7
0
5
Order By: Relevance
“…Although relevant, this value is lower than the average number of complications observed in arthroplasties using constrained implants, which range from 9.2 to 63%. 10,[23][24][25][26][27][28] Most studies demonstrate an incidence of 30 to 40% of complications, the most common being: infections, injuries to the extensor mechanism, and fractures. 10,24,26,29,30 As limitations of our research, we can mention the high number of exclusions, which occurred not only in our study but also in other similar researches that showed a follow-up loss of up to 65%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although relevant, this value is lower than the average number of complications observed in arthroplasties using constrained implants, which range from 9.2 to 63%. 10,[23][24][25][26][27][28] Most studies demonstrate an incidence of 30 to 40% of complications, the most common being: infections, injuries to the extensor mechanism, and fractures. 10,24,26,29,30 As limitations of our research, we can mention the high number of exclusions, which occurred not only in our study but also in other similar researches that showed a follow-up loss of up to 65%.…”
Section: Discussionmentioning
confidence: 99%
“…10,[23][24][25][26][27][28] Most studies demonstrate an incidence of 30 to 40% of complications, the most common being: infections, injuries to the extensor mechanism, and fractures. 10,24,26,29,30 As limitations of our research, we can mention the high number of exclusions, which occurred not only in our study but also in other similar researches that showed a follow-up loss of up to 65%. 18,30 This can be partially explained by the social profile of the patients and the institution where the research was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the selection of articles in which both implants are potentially indicated provides for a more robust comparison. The objectives of this systematic review are: compare the survival rates of a CCK and an RHK [7], compare the differences in clinical outcomes between these two types of implants [8] and evaluate if there is a higher reoperation rate with RHK compared to CCK [9]. We hypothesised that survivorship and clinical outcome at final follow-up would be worse for the RHK prosthesis due to higher constraint.…”
Section: Introductionmentioning
confidence: 99%